Parental Perception of Weight Status for Adenotonsillectomy Patients. (11th February 2021) - Herrmann, Brian W.; Campbell, Kristen; Meier, Maxene; Haemer, Matthew; Crowder, Renee; Tholen, Kaitlyn; Hoefner‐Notz, Regina; Nguyen, Thanh; Friedman, Norman R.
Abstract : Objective: Weight status can affect outcomes in pediatric adenotonsillectomy performed for obstructive sleep disordered breathing. Parents frequently underestimate their child's weight and are unaware weight status may affect adenotonsillectomy success. Accurate understanding of a child's weight status is important for shared decision making with the family and perioperative care. The purpose of this study is to analyze the accuracy of the parent's perception of their child's weight status. Methods: A retrospective analysis was performed of prospective data collected from families of children undergoing adenotonsillectomy from June 2018 through June 2019. Results: A total of 522 children met the inclusion criteria. Two hundred and thirty‐two children were either overweight (n = 46, 9%) or obese (n = 186, 36%). Among parents of this cohort whose children were overweight or obese, 74 (32%) erroneously reported that their child was normal weight. For the 290 nonoverweight children, 99% of parents accurately reported weight status. After adjusting for ethnicity, race, BMI%, and sex, for every 1‐year increase in age of the child, the odds of the parent correctly identifying their child as overweight increased by a factor of 1.18 (95% CI: 1.09, 1.27). Conclusion: One‐third of families with children who were overweight or obese undergoing adenotonsillectomy for obstructive sleep disordered breathing underestimated their child's weight. This study highlights the need to facilitate family understanding of weight status' potential impact on both obstructive sleep disordered breathing severity and adenotonsillectomy success, especially for younger children. Level of Evidence: 4 Laryngoscope, 131:2121–2125, 2021